Curcumin-loaded albumin submicron particles with potential as a cancer therapy: an in vitro study - Suwannasom, Nittiya; Sriaksorn, Netsai; Thepmalee, Chutamas; Khoothiam, Krissana; Prapan, Ausanai; Bäumler, Hans; Thephinlap, Chonthida (Beilstein Journal of Nanotechnology, 2023)
Curcumin (CUR), a polyphenolic compound, shows promising biological properties, particularly antioxidant activity. However, its medical applications are limited due to its low water solubility, bioavailability, and pH-instability. CUR-loaded albumin microparticles (CUR-HSA-MPs) of submicron size in the range of 800 to 900 nm and a zeta potential of −15 mV were prepared. The CUR loading efficiency was up to 65%. A maximum release of 37% of the encapsulated CUR was observed within 6 h when the CUR-HSA-MPs were dispersed in 50% ethanol in PBS at pH 7, while in RPMI 1640 medium the release was 7%. This demonstrates a sustainable release. The in vitro cytotoxicity of CUR-HSA-MPs showed promising anticancer potential against human hepatocellular carcinoma (Huh-7) and human breast adenocarcinoma (MCF-7) cell lines, although this effect was less pronounced in human dermal fibroblasts (HDFB) and human cholangiocyte (MMN) cell lines. Confocal microscopy was used to confirm the uptake of CUR-HSA-MPs by cancer cells. Our studies revealed that HSA-MPs are potentially promising vehicles for increasing the solubility and bioavailability of CUR.
Keywords: albumin submicron particles; cancer therapy; curcumin; drug delivery